Edukasi Pemanfaatan Tanaman Obat Keluarga melalui Media Plant Card (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The low utilization of Family Medicinal Plants (Tanaman Obat Keluarga/TOGA) in RT 14, Wonocatur Hamlet, was identified as a community health issue requiring attention. This community service program aimed to improve residents’ knowledge of the benefits and utilization of TOGA and to promote household self-reliance in maintaining health through promotive and preventive efforts. The program was implemented using a participatory approach, including community meetings, health education through plant card media, demonstrations of TOGA cultivation, and the distribution of TOGA seedling packages (TOGA kits) to residents. Program effectiveness was evaluated using pre-test and post-test assessments to measure changes in participants’ knowledge. The results showed a significant increase in knowledge, with the mean score rising from 80.00 in the pre-test to 96.67 in the post-test (p = 0.003). A total of 11 out of 12 participants experienced score improvement, while no decrease was observed in any participant. In addition, residents showed strong enthusiasm for utilizing the distributed TOGA seedlings. The use of plant card media was proven to support community understanding of essential information related to TOGA. Overall, this intervention was effective in improving community knowledge and participation in the use of TOGA as an independent and sustainable household health resource.